2011
DOI: 10.1001/archoto.2011.178
|View full text |Cite
|
Sign up to set email alerts
|

Using 5-Aminolevulinic Acid and Pulsed Dye Laser for Photodynamic Treatment of Oral Leukoplakia

Abstract: Photodynamic therapy with 5-aminolevulinic acid and pulsed dye laser could be used to achieve regression of oral leukoplakia. The treatment is safe and well tolerated. An application time of 1.5 hours and laser radiant exposure of 8 J/cm(2) with 1.5-ms pulse time were found to be the optimal settings in this study. The high-power laser used in this study allows completion of laser therapy within 1 to 3 minutes. Further studies are necessary to determine the optimal laser radiant exposure and drug application t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 23 publications
1
77
0
1
Order By: Relevance
“…Twenty-three studies, which did not fulfill the eligibility criteria, were excluded (Appendix A). In total, 13 studies [9,[15][16][17][18][19][20][21][22][23][24][25][26] were included and processed for data extraction. The pattern of the present study was customized to mainly summarize the relevant information.…”
Section: Search Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-three studies, which did not fulfill the eligibility criteria, were excluded (Appendix A). In total, 13 studies [9,[15][16][17][18][19][20][21][22][23][24][25][26] were included and processed for data extraction. The pattern of the present study was customized to mainly summarize the relevant information.…”
Section: Search Strategymentioning
confidence: 99%
“…The total number of subjects ranged between 5 patients and 147 individuals. Seven studies [9,15,16,[20][21][22][23] reported the mean age of study participants, which was between 51 years and 62.2 years (age range 30-98 years). Nine studies [9,15,16,[18][19][20][21][22][23] reported the gender of subjects, in which the number of female participants ranged between 0 and 65 individuals.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations